2012
DOI: 10.1007/s11099-012-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring moderate Cu and Cd toxicity by chlorophyll fluorescence and P<sub>700</sub> absorbance in pea leaves

Abstract: We investigated the effect of moderate Cu 2+ and Cd 2+ stress by applying chlorophyll (Chl) fluorescence and P 700 absorbance measurements to monitor the photosynthetic electron transport activity of 3-week-old Pisum sativum L. cv. Petit Provençal plants grown in a modified Hoagland solution containing 50 µM CuSO 4 or 5 µM CdCl 2 . Both heavy metals caused a slight inhibition in PSII photochemistry as indicated by the decrease in the effective quantum efficiency of PSII (Φ PSII ), the maximum electron transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Excess Cu also decreased the active PS II centres of illuminated leaves (Patsikka et al 2002) and resulted in lower photosynthetic electron transport activities (Yruela 2009). Moreover, 50 μM Cu affected the PS II and PS I photochemistry of pea plants (Wodala et al 2012). Additionally, excess Cu decreased the net photosynthetic rate and photosynthetic capacity of barley plants which might be related to mesophyll limitations (Vassilev et al 2002) as well as disturbances of the chloroplast membranes and PS II activity (Vassilev et al 2003).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Excess Cu also decreased the active PS II centres of illuminated leaves (Patsikka et al 2002) and resulted in lower photosynthetic electron transport activities (Yruela 2009). Moreover, 50 μM Cu affected the PS II and PS I photochemistry of pea plants (Wodala et al 2012). Additionally, excess Cu decreased the net photosynthetic rate and photosynthetic capacity of barley plants which might be related to mesophyll limitations (Vassilev et al 2002) as well as disturbances of the chloroplast membranes and PS II activity (Vassilev et al 2003).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 95%
“…There is strong evidence that reduction in chlorophyll biosynthesis is related to structural damages of the photosynthetic apparatus at the thylakoid level under Cu stress (Cisato et al 1997) and interference of Cu with chlorophyll organization (Caspi et al 1999;Wodala et al 2012). Excess Cu also decreased the active PS II centres of illuminated leaves (Patsikka et al 2002) and resulted in lower photosynthetic electron transport activities (Yruela 2009).…”
Section: Effect On Photosynthetic Apparatus and Pigmentsmentioning
confidence: 99%
“…PSI is considered to be sensitive to various environmental stresses [18][19][20][21][22][23][24][27][28][29]. Farhat et al [23] reported that the Mg 2+ deficiency stress applied to Sulla carnosa plants leaves causes an impairment of PSI photochemical activity accompanied by a significant reduction in the abundance of the LHCI antenna and PsaA polypeptides of PSI RC.…”
Section: Introductionmentioning
confidence: 99%
“…Further, several studies showed that PSI complex is also one of the targets of several toxic divalent metal cations such as Cd 2+ , Cu 2+ , Hg 2+ and Pb 2+ . It has been reported that these cations affect photochemical activity, inhibit electron transport between PC and P700 at the donor side, decreased the active P700 content, alter the LHCI antenna and cause a conformational changes of the secondary structure polypeptides of PSI [18,22,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in photosynthetic pigments is likely because of chloroplast damage during development phase upon exposure of Cu in soil system (Ali et al 2015). Kabata-Pendias and Pendias (2001) have presented a strong evidence regarding the chlorophyll biosynthesis reduction which might be linked with the destruction of photosynthetic organization at thylakoid level and also the hindrance of Cu with organized system of chlorophyll (Wodala et al 2012). …”
Section: Cu-induced Phytotoxic Effectsmentioning
confidence: 99%